2008
DOI: 10.1002/chin.200849194
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and Biological Activities of New Hydroxy‐3‐pyrazolyl‐4H‐chromen‐4‐ones and Their O‐Glucosides.

Abstract: Carbohydrates U 0500 Synthesis and Biological Activities of New Hydroxy-3-pyrazolyl-4H-chromen--4-ones and TheirO-Glucosides. -The glucosides (VIII) show greater pharmacological significance than their aglycones (V). -(HATZADE, K. M.; TAILE, V. S.; GAIDHANE, P. K.; HALDAR, A. G. M.; INGLE*, V. N.; Indian J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The results of synthetic work have revealed that maximum yield of compounds (12a-h) was obtained in the cases where chromone nucleus was bearing electron-withdrawing groups at C-6 or C-7. All the synthesized compounds were evaluated by spectral analysis, that is, 1 H-NMR, 13 C-NMR, and Mass spectroscopy. The spectral data of the synthesized compounds 12a-h are given below:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of synthetic work have revealed that maximum yield of compounds (12a-h) was obtained in the cases where chromone nucleus was bearing electron-withdrawing groups at C-6 or C-7. All the synthesized compounds were evaluated by spectral analysis, that is, 1 H-NMR, 13 C-NMR, and Mass spectroscopy. The spectral data of the synthesized compounds 12a-h are given below:…”
Section: Resultsmentioning
confidence: 99%
“…The obtained compounds, that is, substituted 2-(Phenylamino)-3-(1Htetrazol-5-yl)-4H-chromen-4-one derivatives (12a-h) were evaluated for their in vitro antimicrobial activities against different strains of bacteria (S. aureus, Bacillus subtilis, Pseudomonas aeruginosa, and Escherichia coli) and fungi (Aspergillus niger and Candida albicans) as per the reported methods [13,27].…”
Section: Pharmacological Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…are known phytochemical natural products have different pharmacological activities including anticancer, anti-HIV, antimicrobial, antiinflammatory [3,4]. Chalcones are a significant part of plants belonging to the flavonoids family [5].…”
Section: Introductionmentioning
confidence: 99%
“…So, continuation of our work [32][33][34][35][36][37][38] and keeping view of the various biological activities, it was proposed to synthesize new molecules containing thiazole, azomethine, O-glucoside, and sulfonamide moiety in one frame-work.…”
Section: Introductionmentioning
confidence: 99%